(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
Content and Language Integrated Learning (CLIL) is a pedagogical approach that combines the teaching of content subjects with foreign language instruction. This article explores the significance of the CLIL method in foreign language teaching, drawing on research and opinions from prominent scholars in the field.